Density Functional Theory plus U Study of Methanol Adsorption and Decomposition on CuO Surfaces with Oxygen Vacancy - Lu Liu; Peng Gong; Guangcai Shao; Pengfei Liu; Junfeng Wang (Aerosol and Air Quality Research)
Abstract The adsorption and decomposition of methanol (CH3OH) and methoxy radical (CH3O) on CuO(111) were investigated via density functional theory calculations with a Hubbard U correction. The configurations and electronic structures of CH3OH and CH3O adsorbed on CuO(111) surfaces were analyzed. CH3OH molecules were preferentially adsorbed on Cu top sites with OMeOH atoms and H-O3C bonds formed simultaneously. Adsorption on Cu3C sites was more stable than on Cu4C sites, with higher binding energy and shorter Cu-OMeOH and H-OCuO bonds. Stable configurations were also achieved with OMeOH-H bond scission, which were only found on Cu3C and O3C sites. On surfaces with oxygen vacancies, adsorption configurations did not change a lot, while there was increased adsorption energy with shorter bond lengths of Cu-OMeOH and H-OCuO and longer bond lengths of H-OMeOH, indicating the formation of oxygen vacancies enhanced the CH3OH adsorption and H-OMeOH bond scission, and thus accelerated CH3OH decomposition. The dissociative adsorption configuration MeOH-ov3C5 had the highest adsorption energy, at –0.71 eV, with the H-OCuO bond length at 1.00 Å and H-OMeOH at 1.70 Å. Compared with CH3OH, the adsorption energy of CH3O was much higher and reached –1.52 eV in MeO-3C2. The Cu-OMeO and C-OMeO bond distances were 1.80 Å and 1.40 Å, respectively, which were both shorter than CH3OH adsorption. The formation of oxygen vacancies significantly enhanced CH3O adsorption, as CH3O moved to a vacancy and bound with three Cu atoms by OMeO, whose adsorption energy increased to −3.19 eV. Other configurations had OMeO binding with two Cu3C atoms and formed a bridging bond, with adsorption energies of −2.53 and −2.61 eV.